An Analysis of Textbook “ When English Rings a Bell” for Junior High School Grade Eight - Abdul Syahid; Rahmania Ananda; Amanda Salsabila; Sumarni, Sumarni; Florence Angelaila Fauzi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Textbooks are an important learning tool in the education system. It becomes more important when English is learned as a foreign language like in Indonesia. As a language learned other than the mother tongue, most likely English is only learned by Indonesian students in the classroom. As a result, English textbooks have the potential to be students' only access to language in the classroom. The purpose of this study was to find out whether the book